Secularism and its Opponents from Augustine to Solzhenitsyn - Kennedy, E. author. aut Link
X, 278 p.
Keywords: In this overview of secularism and its history, Kennedy traces, through a series of intellectual biographies of leading European thinkers such as Rousseau, Kant, Hegel, Marx, Dostoyevsky, and Solzhenitsyn, just how the Western world changed from religious to secular.